Analisis Gaya Belajar Kinestetik Terhadap Keaktifan Belajar Fisika Siswa Kelas X SMK Negeri 1 Angkola Timur - dewi, dewita rosanti siregar; Eni Sumanti Nasution; Sri Utami Khoilla Mora Siregar (JURNAL PENDIDIKAN ILMU PENGETAHUAN ALAM, 2023)
This study aims to determine the relationship between kinesthetic learning styles and activeness of learning physics in class X student of SMK Negeri 1 Angkola Timur with a total of 25 studentd. The instrument in this study was a kinesthetic learning style questionnaire and active learning. The type in this study was correlation. Data analysis techniques used the normality test, homogeneity, linearity test hypothesis testing using regression and correlation tests. The result showed that there was a positive and significant relationship between kinesthetic learning styles and active learning physics for class X student of SMK Negeri 1 Angkola Timur. Kinesthetic learning (X) with learning activiness (Y) with high correlation criteria, namely 53,3%.